Feasibility study of vehicular heatstroke avoidance system for children - Mohd, Hafiz Jali; Ismail, Amirah; Ahmad Izzuddin, Tarmizi; Sulaima, Mohamad Fani; Mokhtar, Mohd Sulhan (2015)
This paper present the development of Vehicular Heatstroke Avoidance System for Children. The primary objective of this work is to prevent children up to 24 months old from being left unintentionally at the rear seat in closed, parked vehicles, which have the potential to result in heat stroke. The efficacy of heat stroke prevention technologies in sensing the presence of a child in a child restraint and alerting the caregiver if he or she walks away from the car without removing the child is evaluated. This system used motion sensor and sound sensor to detect the unattended children inside the vehicle. Motion detector is used to detect child posture and movement and is integrated as a component of a system that automatically performs a task or alerts a user of motion in an area while sound sensor used to detect sound from the baby. The sensor was attached to the Arduino GSM shield and simulated in IDE software. When the movement of the baby or the baby voice is detected, GSM will send Simple Message System (SMS or text messaging) for alerting the caregiver to attend their children. Vehicular Heatstroke Avoidance system is self-energized device which help in preserving vehicle battery by using solar power. It is expected that this device could help reducing the vehicle heatstroke cases among children that keep on increasing lately.